The Moral Foundations of Left-Wing Authoritarianism: On the Character, Cohesion, and Clout of Tribal Equalitarian Discourse - Lane, Justin E. (Journal of cognition and culture, 2023)
Left-wing authoritarianism remains far less understood than right-wing authoritarianism. We contribute to literature on the former, which typically relies on surveys, using a new social media analytic approach. We use a list of 60 terms to provide an exploratory sketch of the outlines of a political ideology – tribal equalitarianism – with origins in 19th and 20th century social philosophy. We then use analyses of the English Corpus of Google Books (n > 8 million books) and scraped unique tweets from Twitter (n = 202,582) to conduct a series of investigations to discern the extent to which this ideology is cohesive amongst the public, reveals signatures of authoritarianism and has been growing in popularity. Though exploratory, our results provide some evidence of left-wing authoritarianism in two forms: (1) a uniquely conservative signature amongst ostensible liberals using measures derived from Moral Foundations Theory and (2) a substantial prevalence of anger, relative to anxiety or sadness, in tweets analyzed for sentiment. In general, results indicate that this worldview is growing in popularity, is increasingly cohesive, and shows signatures of authoritarianism.